Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Detection of Echovirus 11 lineage 1 in wastewater samples in Sicily - Giovanni M. Giammanco; Chiara Filizzolo; Mariangela Pizzo; Giuseppa L. Sanfilippo; Federica Cacioppo; Floriana Bonura; Stefano Fontana; Gabriele Buttinelli; Paola Stefanelli; Simona De Grazia (Science of The Total Environment, 2024)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)